THE USE OF CUE CARD IN TEACHING SPOKEN DESCRIPTIVE TEXT (Journal of Research and Educational Research Evaluation, 2012)
Speaking is verbal language to deliver ideas. Expressing thoughts, feeling, even feeling simply being together can be got through speaking. Many English classes in Indonesia tend to use their L1 rather than practicing English well. This condition can be worst, if teachers neglect the technique such as using media in teaching speaking. Cue Cards is one of the media to encourage students speak well in the classroom. It can attract students to be more participated in the speaking class. This article discusses about the use of cue card as the medium in the speaking class, in the form of descriptive text. As cue card is very visible, when students see these cue cards, they can describe someone / something easily. The result shows that using cue card in speaking maintains students to reach high score in spoken descriptive text.